Edukasi Kesehatan Reproduksi bagi Remaja Masa Kini - Srihadi Yanti, Entin; Risnasari, Norma; Nurahmawati, Dhewi; Wulaningtyas, Eko Sri; Mulazimah, Mulazimah; Puspitasari, Oktavia; Purnamasari, Ririn Ita; Rahmadini, Siska Nuriya (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Teenagers have a proportion of 17% of the total population of Indonesia. Adolescence is a transition from children to adults between the ages of 10 till 18 years. Adequate access to information can help adolescents avoid the threats of today's youth. One effort to increase knowledge in counseling. This activity aims to increase adolescents' knowledge regarding reproductive health in Sepawon Village, Plosoklaten District, Kediri Regency. Activities carried out by the method of lectures, discussions and games. Activity evaluation is obtained by comparing the pre-test and post-test scores. The activity results showed an increase of 25% in adolescents' knowledge after participating in Adolescent Reproductive Health Extension activities. With the implementation of this activity, it is hoped that similar activities can be carried out routinely by involving various sectors, such as the government, health services, puskesmas and NGOs, so that adolescent development can take place optimally and avoid the current threat of youth.